Pendidikan Kesehatan Terhadap kesiapan pemulangan Pasien TB - Fatmawati Mohammad; Fakhriatul Falah; Muhamad Irfandi Saleh (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2021)
Background: A large number of reccurence in pulmonary TB patients is due to a lack of knowledge to perform self-care at home, which is assumend as a lack of readiness of pulmonary TB patients when facing discharge. Health education can increase knowledge, willingness, and community role in preventing pulmonary TB disease. Objective: The research aimed at determining the effect of health education towards discharge readiness of pulmonary TB patients at Interna Ward II of RSUD Toto Kabila, Bone Bolango District. Methods:This research applied Pre-Experimental design with One Group Pretest-Posttest design. The research samples were 23 respondents with the purposive sampling method. Results: Research finding based on the Wilcoxon statistical test revealed that there was a significant change in the knowledge before and after was given health education with the p-value = 0,000. Conclusion: It can be concluded that there was an effect of healt education towards discharge readiness of pulmonary TB patients at Interna Ward II of RSUD Toto Kabila,Bone Bolango District.